PENGARUH LAMA PENYIMPANAN TELUR HERBAL AYAM RAS FASE KEDUA PADA SUHU RUANG TERHADAP PENURUNAN BERAT TELUR, DIAMETER RONGGA UDARA, DAN INDEKS ALBUMEN - Masitoh Masitoh; Khaira Nova; Rudy Sutrisna; RR Riyanti (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2022)
This study aimed to determine the effect of storage time of the second phase of chicken herbal eggs at room temperature on egg weight loss, air cell diameter, and albumen index and also to determine the best storage time for second phase of chicken herbal eggs. This research was conducted on 7 October until 4 November 2020 at the Animal Production Laboratory, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. This study used a completely randomized design (CRD) with 5 treatments of storage time for herbal eggs for 0, 1, 2, 3, 4 weeks and 4 replications. In each treatment, 12 herbal eggs were used with the total number of herbal egg samples used as many as 60 eggs. The data obtained were tested according to analysis of variance. If there is a significant effect, the Least Significant Difference (LSD) test is carried out at the 5% level. The results of this study indicated that the herbal egg storage treatment had a significant effect (P <0.05) on reducing egg weight, air cell diameter, and albumen index. The storage time of 1 week gave the best effect on the lowest egg weight reduction which was 2,696% ± 0.713, the smallest air cell diameter which was 2.199 ± 0.137 cm and the highest index value albumen which was 0.023 ± 0.004 compared to the storage time of 2, 3 and 4 weeks. Keywords: Air cell diameter, Albumen index, Egg weight loss, Herbal egg, Room temperature